On the “Modelling of business, industrial and transport systems” international conference - Kopytov, Eugene; Pranevičius, Henrikas; Yatskiv, Irina (Technological and Economic Development of Economy, 2008)
On the “Modelling of business, industrial and transport systems” international conference Technological and Economic Development of Economy, 14(3), 244–246. First published online: 21 Oct 2010